Mahmud Yunus Thoughts on Functional Objectives in Arabic Language Learning: Its Application in Indonesian Islamic Boarding School | Afkār Mahmūd Yūnus fī Al-Ahdāf Al-Wadzīfīyah Lita - Muhammad Yusuf Salam; Yovan Luksfinanto; M Abdul Hamid (Universitas Islam Negeri Palangka Raya, 2022)
This study aims to reveal Mahmud Yunus' ideas about functional Arabic learning objectives, and the application of Arabic learning objectives based on Mahmud Yunus' ideas at Gontor Modern Islamic Boarding School 9. This study used a qualitative design with two approaches: library research and case study. Research data were obtained through documentation, observation, and in-depth interview. The verification of the correctness, applicability, and reliability of the data was carried out through data triangulation. This study resulted in the following conclusions: 1) the purpose of learning functional Arabic was to use social, practical, and natural functions as a tool to master listening skills (understanding spoken language), reading (understanding written language), oral expression and written expression, 2) the application of Mahmud Yunus thoughts on the objectives of teaching Arabic in modern Islamic boarding schools in Gontor was illustrated in language, cultural, and communicative goals. The conclusion of the research illustrates that the objectives of learning Arabic from the perspective of Mahmud Yunus and its implementation in Gontor Modern Islamic Boarding School is to use social, practical, and natural functions as a tool in realizing the objectives of learning Arabic which are language, cultural, and communicative goals.